Exploration of the roles of spoilage bacteria in degrading grass carp proteins during chilled storage: A combined metagenomic and metabolomic approach. (February 2022) - Zhuang, Shuai; Tan, Yuqing; Hong, Hui; Li, Dapeng; Zhang, Longteng; Luo, Yongkang
Graphical abstract: Highlights: Aeromonas rivipollensis degraded myofibrillar proteins especially myosin heavy chain. Shewanella putrefaciens was active in hydrolyzing fish proteins especially collagens. Pseudomonas putida was active in absorbing oligopeptides and free amino acids. Shewanella could produce putrescine through the arginine decarboxylase pathway. Serine and arginine in fish flesh were largely consumed by three inoculated bacteria. Abstract: Protein degradation 1 caused by spoilage bacteria is highly related to fish quality deterioration during chilled storage. However, the exact roles of bacteria in degrading grass carp proteins are not fully known. In this work, we used metagenomics to analyze the microbiota composition in grass carp fillets, construct protein degrading pathways, and calculate taxonomic contributions to protein degrading functions. Besides, three dominant bacteria species were isolated and inoculated into sterile grass carp flesh, respectively. LC-MS-based untargeted metabolomics was then used to detect protein degradation metabolites produced by the inoculated bacteria. Combining the results of metagenomics and metabolomics, we found 1) Shewanella putrefaciens was active in hydrolyzing fish proteins (especially collagens) and produced quantities of putrescine through the arginine decarboxylase pathway; 2) Pseudomonas putida had potent potentials in utilizing oligopeptides and free amino acids; 3) Serine was a potential energy source for microbial growth and it was largely consumed by spoilage bacteria; 4) S. putrefaciens could form a metabiosis relationship with P. putida, due to their complementary roles in degrading fish proteins. Finally, we concluded that S. putrefaciens had the strongest spoilage potential among tested bacteria, suggesting the importance of S. putrefaciens inhibition in fish quality preservation. Meanwhile, this study contributed to a better understanding of microbial roles in fish spoilage and provided useful information for the development of new preservation methods.